2014
DOI: 10.1186/s40461-014-0003-3
|View full text |Cite
|
Sign up to set email alerts
|

A study of carpenter apprentices’ spatial skills

Abstract: Background: Spatial skills are crucial for carpentry and are a major learning objective in the initial vocational training of carpenter apprentices. Carpenters specifically need to develop the capability to switch between two-dimensional (2D) and three-dimensional (3D) representations. Previous studies have explored spatial skills, but never in the context of vocational education and training (VET). This study sheds light on the level and evolution of spatial skills in the initial vocational training of carpen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In the previous study on spatial skills training, Uttal et al (2013) found that spatial skills were "moderately malleable and that training, on average, improved performance by almost half a standard deviation" [8]. This evidence also helps explain why well-experienced hand in furniture carpentry has obvious advantages in judgements and keenness of spatial views compared with beginners [9], in a result which is by long-term accumulation of experience in practice [6], [10], therefore, it has been proved that the promotion in judgements of spatial awareness is of tremendous help to furniture design and fabrication [2].…”
Section: A Importance Of Spatial Skillsmentioning
confidence: 94%
See 3 more Smart Citations
“…In the previous study on spatial skills training, Uttal et al (2013) found that spatial skills were "moderately malleable and that training, on average, improved performance by almost half a standard deviation" [8]. This evidence also helps explain why well-experienced hand in furniture carpentry has obvious advantages in judgements and keenness of spatial views compared with beginners [9], in a result which is by long-term accumulation of experience in practice [6], [10], therefore, it has been proved that the promotion in judgements of spatial awareness is of tremendous help to furniture design and fabrication [2].…”
Section: A Importance Of Spatial Skillsmentioning
confidence: 94%
“…For beginners, the preliminary difficulty is 2D view judgements of furniture, lacking spatial senses of 3D subject and experience of mortice-tenon fabrication. It is difficult for 2D views' judgement in furniture making [2], finally influencing materials cutting and making errors in fabrication and assembling of mortice structures. Spatial views judgement is the primary technique for furniture fabrication learning in the course of furniture carpentry [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, vocational education learns materials that are more specific. Stated that vocational education is an overall experience concept for every individual who learns for their success at workplaces [2] [3].…”
Section: Introductionmentioning
confidence: 99%